2016
DOI: 10.1186/s40659-016-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Reprimo as a modulator of cell migration and invasion in the MDA-MB-231 breast cancer cell line

Abstract: BackgroundReprimo (RPRM), a highly glycosylated protein, is a new downstream effector of p53-induced cell cycle arrest at the G2/M checkpoint, and a putative tumor suppressor gene frequently silenced via methylation of its promoter region in several malignances. The aim of this study was to characterize the epigenetic inactivation and its biological function in BC cell lines.MethodsThe correlation between RPRM methylation and loss of mRNA expression was assessed in six breast cancer cell lines by methylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In this study, we show for the first time that the CHL1 gene, located in this region, is silenced in a subset of invasive BC cases due to promoter hypermethylation, but not in adjacent-to-tumour tissue and non-neoplastic tissue from mammoplasties. This epigenetic alteration has been found by pyrosequencing, a technique that yields quantitative measurements of methylation in contrast to methylation-specific PCR [2933]. Consistent with the observed hypermethylation, we have found that tumour cells in BC tissues have a lower level of CHL1 expression compared with non-neoplastic adjacent-to-tumour cells.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we show for the first time that the CHL1 gene, located in this region, is silenced in a subset of invasive BC cases due to promoter hypermethylation, but not in adjacent-to-tumour tissue and non-neoplastic tissue from mammoplasties. This epigenetic alteration has been found by pyrosequencing, a technique that yields quantitative measurements of methylation in contrast to methylation-specific PCR [2933]. Consistent with the observed hypermethylation, we have found that tumour cells in BC tissues have a lower level of CHL1 expression compared with non-neoplastic adjacent-to-tumour cells.…”
Section: Discussionsupporting
confidence: 88%
“…Interesting results were proposed by Buchegger et al [ 85 ]. They suggested potential mechanism of migration of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Correspondingly, mouse xenografts models of gastric cancer cells deficient in RPRM expression have demonstrated enhanced tumor formation and volume [ 31 , 32 ]. In other tumors, such as breast cancer, pituitary tumors and renal cell carcinoma cell lines, overexpression of RPRM suppresses cell proliferation, cell migration, clonogenic capacity and invasiveness [ 33 , 34 , 35 ]. Furthermore, the role of RPRM in cell-cycle has also been explored.…”
Section: Role Of the Rprm Gene Family In Human mentioning
confidence: 99%